Pengaruh Ekstrak Pegagan (Centella asiatica) terhadap Ekspresi IL-1β pada Tikus Diabetes Melitus Tipe 2 - Fitria Dhenok Palupi; Annisa Avelia (JURNAL RISET GIZI, 2025)
Background: Type 2 diabetes mellitus (T2DM) is characterized by chronic hyperglycemia and low-grade inflammation that disrupts cytokine production, including interleukin-1β (IL-1β), which plays a key role in β-cell function and survival. Objective: This study aimed to investigate the effect of Centella asiatica ethanol extract on IL-1β expression in streptozotocin–nicotinamide (STZ-NA)–induced type 2 diabetes mellitus (T2DM) rat models. Method: The study employed a randomized post-test-only controlled group design involving 48 male Wistar rats, which were randomly allocated into six experimental groups, including two control groups. Observations and outcome measurements were conducted on days 28 and 35. Treatments included Centella asiatica extract at doses of 300, 600, and 1200 mg/kgBW and metformin as a comparison. IL-1β expression was assessed using immunohistochemistry and scored using the Immunoreactive Score (IRS). Data were analyzed using the Kruskal–Wallis and Mann–Whitney tests. Results: Results showed that STZ-NA induction decreased IL-1β expression compared with normal controls. Administration of Centella asiatica extract significantly influenced IL-1β expression (p < 0.05). The 1200 mg/kgBW dose restored IL-1β expression to levels comparable with the normal control and metformin groups, especially at 35 days. Conclusion: In conclusion, Centella asiatica ethanol extract improves impaired cytokine production in T2DM rats, and the 1200 mg/kgBW dose for 35 days demonstrates the strongest effect in normalizing IL-1β expression.